2003
DOI: 10.3928/0098-9134-20030401-10
|View full text |Cite
|
Sign up to set email alerts
|

Health Screening Practices IN RURAL LONG-TERM CARE FACILITIES

Abstract: This report summarizes the descriptive data collected and analyzed as part of a larger study examining an educational intervention related to health screening practices in long-term care (LTC) facilities in a rural Midwestern state. The health screening practices examined were prostate-specific antigen testing, manual prostate examination, breast self-examination, clinical breast examination, and mammography. A review of the literature reveals health-screening practices are not being adequately provided to old… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…This may especially apply to persons in nursing homes. 20 That other studies of PD and cancer did not include negative comparison controls limits interpreting the associations observed, both the inverse findings [1][2][3][4]8,9,11,12 and a recent study 10 which found adverse associations between PD and cancers in Taiwan, as health care systems may vary widely in the aggressiveness with which cancer screening and medical work-ups are pursued in those already confronting a medically debilitating condition. Thus, our findings of reduced risk of cancer after both automobile accidents and PD are consistent with under-ascertainment of cancer after at least some unrelated health outcomes.…”
Section: Discussionmentioning
confidence: 94%
“…This may especially apply to persons in nursing homes. 20 That other studies of PD and cancer did not include negative comparison controls limits interpreting the associations observed, both the inverse findings [1][2][3][4]8,9,11,12 and a recent study 10 which found adverse associations between PD and cancers in Taiwan, as health care systems may vary widely in the aggressiveness with which cancer screening and medical work-ups are pursued in those already confronting a medically debilitating condition. Thus, our findings of reduced risk of cancer after both automobile accidents and PD are consistent with under-ascertainment of cancer after at least some unrelated health outcomes.…”
Section: Discussionmentioning
confidence: 94%
“…From the expanded electronic database search, we identified 26 articles for analysis. Four articles (Bassett & Smyer, 2003; MacDonald, Sarna, Uman, Grant, & Weitzel, 2006; Oliffe, 2007; Setter, Corbett, Campbell, Cook, & Gates, 2003) used the biological marker conceptually and explored its use from an educational or practice perspective (e.g., the meaning of hemoglobin A1c to patients or providers), rather than its specific use as a variable of interest in the research analysis, thus they were excluded from this review. This left 22 articles for full review and analysis.…”
Section: Synthesis Of Nurse-led Aging Research Using Biomarkersmentioning
confidence: 99%